Comparação de custos entre cargos extintos na Administração Pública e terceirização de mão de obra: um estudo de caso com motoristas na Universidade Federal do Triângulo Mineiro- UFTM - CALDEIRA, Luiza Barbosa (2018)
From the moment Law 13429 was sanctioned, several questions about outsourcing arose due to different reasons, such as the possibility of an organization to outsource supporting activities as well as the core activity. Given the new-found possibilities made possible by outsourcing, it is paramount understanding how this factor into cost reduction, seen as one of the main reasons to adopt such a model, and if it is actually factual. This study was conducted as to answer if outsourcing supporting activities is a more viable option, from the point of view of costs, than to have civil servants in Public Administration. Therefore, a case study was carried out within Universidade Federal do Triângulo Mineiro - UFTM, where expense information was collected from January 2013 up to December 2017 with the acting drivers within the institution, a position chosen as the object of study. Data were collected through bibliographical and documental research, through articles, undergraduate theses, reports, laws, decrees. The comparative method was applied, and the quantitative research approach was used. The results of the research pointed out that the outsourcing services for the driver's position, in fact, had a lower cost than of the civil servant. In addition,that for the contracting of outsourced service provision, the replacement of labor, retirement and others should be taken into consideration.